If you mean: 3x+y-x+y then it is an algebraic expression that can be simplified to 2x+2y
If y = 0 then yx - 5 = 0*x - 5 = 0 - 5 = -5
3x - y = 12 is the same as 3x - 12 = y, or y = 3x - 12.
y = 3x 3x + 4y = 30 3x + 4(3x) = 30 3x + 12x = 30 15x = 30 x = 2 y = 3x y = 3(2) y = 6 (2, 6)
-2
3x-y to the third becomes (x+x)+x-y*y*y the question is (3x-y)3
x + y = -4x - y = 2x - y = 2x + y - y = 2 + yx = 2 + yx + y = -42 + y + y = -42 + 2y = -42 - 2 + 2y = -4 - 22y = -62y/2 = -6/2y = -3x = 2 + yx = 2 - 3x = -1The solution of the system is (-1, -3)
6x - 2y + 3xz - yz = (z + 2)(3x - y) 9x - 3y = 3(3x - y) (3x - y) over (3x - y) equals 1, so they can be canceled out. The simplified expression is (z + 2) over 3.
The problem to solve is: xy+x+3y+3 Multiply y and x Multiply the y and x Multiply y and x The y just gets copied along. The x just gets copied along. The answer is yx yx x*y evaluates to yx x*y+x evaluates to yx+x Multiply y and 3 Multiply y and 1 The y just gets copied along. The answer is y y 3*y evaluates to 3y The answer is yx+x+3y x*y+x+3*y evaluates to yx+x+3y The answer is yx+x+3y+3 x*y+x+3*y+3 evaluates to yx+x+3y+3 ---- The final answer isyx+x+3y+3----
If y = 0 then yx - 5 = 0*x - 5 = 0 - 5 = -5
x=y/7
x=y/7
What is the solution set for the equations x-y=2 and -x+y=2
3x - y = 4 Get y by itself to see if it is the same as y = 3x - 4: 3x = 4 + y 3x - 4 = y Therefore, 3x - y = 4 is the equivalent of y = 3x - 4.
-9
your equation is y=3x + 4 here are five parallel equations... y=3x + 5 y=3x + 6 y=3x + 7 y=3x + 8 y=3x + 9
y = 3x + 1 y = 3x + 2 y = 3x + 3 y = 3x
No. There is no equality (or inequality) in the question: only a list of expressions.